1977
DOI: 10.1161/01.res.40.4.401
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic control of cardiovascular functions during neonatal development and in adult sheep.

Abstract: SUMMARY We studied the autonomic control of resting heart rate and of systemic and pulmonary vascular blood pressures (BP) in chronically instrumented neonatal lambs 1-8 weeks of age. The maximum response to ganglionic blockade and sympathetic and parasympathetic antagonists was taken as an index of the magnitude of the total neural, adrenergic, and cholinergic tones. The reactivity of the circulatory parameters to adrenergic and cholinergic agonists also was investigated. All findings were compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
44
1
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 25 publications
10
44
1
2
Order By: Relevance
“…In the present study, basal MAP 1 wk postnatal was almost twice that reported in fetal sheep (1,7,9,31), and values continued to rise until after the second week postnatal. This pattern is consistent with other studies in neonatal sheep (38,39) and more recent data in preterm neonates (40). This secondary rise in MAP is not well studied and could reflect several mechanisms, including decreases in circulating levels of fetally derived vasodilators, increases in PVR due to enhanced vascular reactivity or increased plasma levels of vasoconstrictors, and/or increases in cardiac output.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, basal MAP 1 wk postnatal was almost twice that reported in fetal sheep (1,7,9,31), and values continued to rise until after the second week postnatal. This pattern is consistent with other studies in neonatal sheep (38,39) and more recent data in preterm neonates (40). This secondary rise in MAP is not well studied and could reflect several mechanisms, including decreases in circulating levels of fetally derived vasodilators, increases in PVR due to enhanced vascular reactivity or increased plasma levels of vasoconstrictors, and/or increases in cardiac output.…”
Section: Discussionsupporting
confidence: 91%
“…There also were parallel dose-dependent increases in FmVR, but, as with MAP, responses were unchanged with age. This suggests that vascular reactivity is unchanged during the study period, which is consistent with earlier reports (29,38), or that vascular sensitivity increases; however, potential increases in the clearance and/or distribution of ANG II in the first month postnatal may result in similar pressor responses at all ages. Thus, Wilson et al (29) suggested that one had to use the plasma level of ANG II rather than the dose infused to evaluate age-dependent changes in newborn sheep, implying that ANG II clearance increases during the postnatal period and is agedependent.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Considerable controversy has been raised regarding the potential effectiveness of P-adrenoreceptor agents in increasing myocardial performance during the newborn period (7,10,(29)(30)(31)(32). We have entertained the possibility that the main mechanism by which P-adrenergic agonists increased cardiac output in the neonate is through their effects in increasing heart rate rather than increasing contractility.…”
Section: Discussionmentioning
confidence: 99%